(untitled) (Economics and region, 2022)
Changes taking place in society lead to the need for changes in the formation and implementation of state social policy. Social policy should be considered as an activity to regulate relations of equality between different individuals and social groups of society. The goal of the social policy of the state is the formation of a stable and highly developed society in which there are no sharp social contrasts, an acceptable standard of living and quality of life are achieved, conditions for the development of human potential are ensured, there is a sufficient degree of social agreement and social solidarity, and social contradictions are resolved without acute conflicts . It was noted that social policy plays an important role in ensuring the stable development of society. By creating conditions for the free and equal activity of citizens, the state, with the help of social policy, reduces social tension in society, which allows it to develop more sustainably. Accordingly, the development of mechanisms for the rational use of resources allocated for social purposes becomes an urgent issue. It was established that the main priorities in social policy should be: raising the level and quality of life through strengthening the role of wages, improving labor relations and employment of the population; social protection of the population; improvement of pension provision through the strengthening of insurance principles, establishing a close dependence of the size of pensions on earnings and insurance experience; improvement of the demographic situation; youth policy. The main characteristics of a welfare state according to the new concept are outlined: the presence of a social insurance system; the existence of budgetary social payments; the existence of state systems of social protection, social security and employment security; availability of social support to all members of the society without exception; acceptance by the state of responsibility for the level of well-being of citizens; the existence of civil society institutions. It was determined that the main condition for the effective implementation of the new model of social policy is to provide adequate opportunities for different segments of the population to open their own businesses with the aim of increasing the GDP, increasing the number of taxpayers and expanding the tax base, improving the macroeconomic indicators of the country.